Diversité microbienne associée au cycle du méthane dans les mares de fonte du pergélisol subarctique - Crevecoeur, Sophie (Université Laval, 2016)
The thawing and collapse of ice-rich permafrost in the subarctic region of Quebec has given rise to thaw ponds (thermokarst ponds) that emit the greenhouse gases carbon dioxide and methane to the atmosphere. However, the microbial community composition that underlies biogeochemical processes in thaw ponds has been little investigated, particularly concerning the diversity and activity of micro-organisms involved in the methane cycle. The objective of this thesis study was to determine the phylogenetic and functional diversity of micro-organisms in subarctic thaw ponds, and the relationships with environmental properties and methane emission. To that aim, we sampled ten thaw ponds in four different valleys located across a permafrost degradation gradient with distinct physico-chemical properties. Depending on valley, the ponds were derived either from the thawing of a palsa (peat-mound) or lithalsa (mineral-mound), which influenced the nature of organic carbon available for microbial remineralization. During summer, the ponds were observed to be well-stratified; there were with strong physico-chemical gradients down the water column, with an upper oxic layer and a bottom low oxygen or anoxic layer. To identify the factors influencing microbial community composition, we used high throughput sequencing techniques targeting transcripts of 16S rRNA gene, and additionally targeted genes involved in the methane cycle: mcrA for methanogenesis and pmoA for methanotrophy. As a proxy of microbial activity, we also measured the concentration of functional gene transcripts using with quantitative PCR (qPCR). The results showed a striking dominance of micro-organisms involved in the methane cycle, namely methanogenic Archaea and methanotrophic Bacteria. The pmoA analyses implied that methanotrophic Bacteria were not only active in the surface, but also in the bottom waters where oxygen concentrations were minimal; this was unexpected given their need for oxygen in methane consumption. In general, the microbial community ...